Predictable Patterns after Large Stock Price Changes on the Tokyo Stock Exchange - Bremer, Marc; Hiraki, Takato; Sweeney, Richard J. (Journal of Financial and Quantitative Analysis, 1997)
Marc Bremer, Takato Hiraki, Richard J. Sweeney, Predictable Patterns after Large Stock Price Changes on the Tokyo Stock Exchange, The Journal of Financial and Quantitative Analysis, Vol. 32, No. 3 (Sep., 1997), pp. 345-365